Cognitive Skills, Noncognitive Skills, and School-to-Work Transitions in Rural China - Paul Glewwe; Qiuqiong Huang; Albert Park (Institute of Labor Economics (IZA), 2017)
Economists have long recognized the important role of formal schooling and cognitive skills on labor market participation and wages. More recently, increasing attention has turned to the role of personality traits, or noncognitive skills. This study is among the first to examine how both cognitive and noncognitive skills measured in childhood predict educational attainment and early labor market outcomes in a developing country setting. Analyzing longitudinal data on rural children from one of China's poorest provinces, we find that both cognitive and noncognitive skills, measured when children are 9-12, 13-16, and 17-21 years old, are important predictors of whether they remain in school or enter the work force at age 17-21. The predictive power of specific skill variables differ between boys and girls. Conditioning on years of schooling, there is no strong evidence that skills measured in childhood predict wages in the early years of labor market participation.
Keywords: I25; J16; J24; O53; 330; cognitive skills; noncognitive skills; school-to-work transition; schooling; rural China